Phytochemical Screening and Antimicrobial Activity Of Asparagus Racemosus Willd. and Asparagus Curillus Buch.-Ham. Ex Roxb - Shrestha, Rose; Shakya, Astha; Shrestha, Krishna Kumar (Journal of Natural History Museum, 2018)
Asparagus racemosus Willd. is an important medicinal plant of tropical and subtropical regions of Nepal and India. Its medicinal usage has been reported in the Indian and British Pharmacopoeias and in traditional systems of medicine such as Ayurveda, Unani, and Siddha. Asparagus curillus Buch-Ham.ex Roxb. is also one of the species found in higher altitude of Nepal. Its roots are used as substitute for A. racemosus. Phytochemical investigation was done for these two species of Nepalese Asparagus as per Methodology for Analysis of Vegetable Drugs by I. Ciulei.1982. Phytochemical screening revealed the presence of coumarin, flavonoid, catecholic tannin, reducing compound in alcoholic extract of A. racemosus while its aqueous extract revealed polyuronoid, reducing compound, polyoses, saponin, gallic tannin, catecholic tannin, etc. Similarly, alcoholic extract of A. curillus revealed catecholic tannin, reducing compound and aqueous extract revealed polyuronoid polyoses, saponin, gallic tannin as main phytochemical compounds. Comparative antimicrobial activity of ethanolic extract of these two species has been evaluated using Kirby-Bauer Agar well diffusion method. The extracts were screened for their antimicrobial activity on nine different strains of human pathogenic microorganisms such as Escherichia coli, Salmonella typhi, Bacillus subtilis, Pseudomonas aeruginosa, Staphylococcus aureus, Klebsiella pneumoniae, Enterococcus faecalies, Saccharomyces cerevisiae and Candida albicans. Among them A. racemosus has shown selected antimicrobial effects against B. subtilis, E. coli, E. faecalis, S. cerevisiae and C. albicans with zone of inhibition of 25 mm in an average. While A. curillus showed effects on S. cerevisiae and C. albicans only with zone of inhibition about12 mm. J. Nat. Hist. Mus. Vol. 29, 2015, Page: 91-102